Al-manhaj al-Qur'ani (the Qur'anic methodology) in dealing with others: an exegetical analysis of selected verses - Shehu, Fatmir Mehdi (2021)
This seminar paper deals with an important subject, entitled “Qur’anic Methodology in Dealing with Others in light of exegetical analysis of selected verses.” Its goal is to explore the methodologies mentioned in the Qur’an, which are used directly or indirectly as a means in dealing with others. This subject is very significant as it offers an exegetical analysis of the selected Qur’anic Text in order to extract appropriate methodologies relevant to the needs of contemporary global society. This seminar paper discusses the meaning of al-Qur’an as the Divine Source of Knowledge, the Qur’anic Methodologies, namely: descriptive, objective, analytical, critical, comparative, argumentative, and travelogue, and the illustration of one selected Qur’anic Methodology. The descriptive, analytical and comparative methods are used in the deliberation of this topic. It is hoped that this Online Seminar provides for the participants the Qur’anic Methodology to be used by them in their day-to-day lives. Also, it enables them to differentiate between the Qur’anic methodology and other types of methodologies presented by other religions and human ideologies.